Electrodeposited Ni-Co-Sn alloy as a highly efficient electrocatalyst for water splitting. (29th March 2019) - Liu, Yuchan; Lu, Hongxia; Kou, Xinli
Abstract: Water splitting to produce hydrogen and oxygen is considered as a feasible solution to solve the current energy crisis. It is highly desirable to develop inexpensive and efficient electrocatalyst for both the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). In this paper, nanostructured Ni-Co-Sn alloys were electrodeposited on copper foil and the excellent electrocatalytic performances for both HER and OER in alkaline media were achieved. The optimized Ni-Co-Sn electrode shows a low onset overpotential of −18 mV and a small Tafel slope of 63 mV/dec for the HER, comparable to many state-of-the-art non-precious metal HER catalysts. For the OER, it produces an overpotential of 270 mV (1.50 V vs . RHE) at current density of 10 mA/cm 2, which is better than that of the commercial Ir/C catalyst. In addition to high electrocatalytic activities, it exhibits good stability for both HER and OER. This is the first report that Ni-Co-Sn is served as a cost-effective and highly efficient bifunctional catalyst for water splitting and it will be of great practical value. Highlights: Nanostructured Ni-Co-Sn alloy electrode was prepared by electrodeposition. It showed excellent catalytic activity and good stability for both HER and OER. The origin of excellent electrocatalytic performance of Ni-Co-Sn was elucidated.